INFANTICIDE IN O’NEILL’S DESIRE UNDER THE ELMS - Sarif Syamsu Rizal (Dinamika Bahasa dan Budaya, 2010)
This study aims to discuss “Infanticide in Eugene O’Neill’s Desire under the Elms” as an alternative understanding of literary text-oriented approach. The study explores O’Neill’s Desire under the Elms through analyzing its interrelated intrinsic elements within such as character, conflict, setting, and theme This study examines the intrinsic elements O’Neill’s Desire under the Elms by applying structural approach. The series of analysis is conducted to find out the description of two protagonists, finding out the conflicts happened among them, finding out the setting by describing environment, and finding out the theme referring to the previous problems. Finally, the result of this study shows the motives, based on the focusing on character, conflict, and setting, driving to practice infanticide done by Abbei in Eugene O’Neill’s Desire under the Elms. Keywords: infanticide, protagonist, conflict, motives